2017
DOI: 10.1016/j.oooo.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The bone regenerative capacity of canine mesenchymal stem cells is regulated by site-specific multilineage differentiation

Abstract: Objectives Mesenchymal stem cells (MSCs) are promising therapies in dentistry due to their multipotent properties. Selecting donor MSCs is crucial because beagle dogs (canines) commonly used in pre-clinical studies have shown variable outcomes and it is unclear whether canine MSCs (cMSCs) are skeletal site-specific. This study tested whether jaw and long bone cMSCs have disparate in vitro and in vivo multilineage differentiation capabilities. Study Design Primary cMSCs were isolated from mandible (M-cMSCs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…This is partly due to the distinct structures of alveolar bone, characterized by compact, wide, and highly mineralized trabeculae and less bone marrow (Zhou et al 2018). In addition, several in vitro studies demonstrated that SSCs from alveolar bone have a strong osteogenic potential (Akintoye et al 2006; Bugueño et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the distinct structures of alveolar bone, characterized by compact, wide, and highly mineralized trabeculae and less bone marrow (Zhou et al 2018). In addition, several in vitro studies demonstrated that SSCs from alveolar bone have a strong osteogenic potential (Akintoye et al 2006; Bugueño et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bone lesions may display unique histological changes in the jawbones. Craniofacial bone development is different from long bones and that it develops from neural crest [27] , [13] , [10] , [28] , [29] . This difference may also be effective in immunostaining results.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin is a class VI intermediate filament protein; it is known as a specific marker of neural or neural crest stem cells [10] , [13] , [27] , [28] , [29] . Nestin, which tends to be more strongly expressed in mandibular bone morphogenetic stem cells (R).…”
Section: Methodsmentioning
confidence: 99%
“…currently, the canine mandible defect model is widely used in preclinical studies (25)(26)(27). Notably, beagle dogs are recommended as potential animal models for medical testing due to their genetic, biological and behavioral characteristics that closely resemble those of humans; furthermore, numerous symptoms of human conditions can be replicated in dogs (28). Previous studies comparing canine and human dental mesenchymal stem cells have demonstrated that canine dPScs were able to differentiate into odontoblast-like cells exhibiting osteogenic potential similar to human dPScs (29).…”
Section: Bidirectional Ephrinb2-ephb4 Signaling Regulates the Osteogementioning
confidence: 99%